Identification of rare microbial colonizers of plastic materials incubated in a coral reef environment - Singleton, Sebastian L.; Davis, Edward W.; Arnold, Holly K.; Daniels, An Mei Y.; Brander, Susanne M.; Parsons, Rachel J.; Sharpton, Thomas J.; Giovannoni, Stephen J. (Frontiers in Microbiology, 2023)
Plastic waste accumulation in marine environments has complex, unintended impacts on ecology that cross levels of community organization. To measure succession in polyolefincolonizing marine bacterial communities, an in situ time-series experiment was conducted in the oligotrophic coastal waters of the Bermuda platform. Our goals were to identify polyolefin colonizing taxa and isolate bacterial cultures for future studies of the biochemistry of microbeplastic interactions. HDPE, LDPE, PP, and glass coupons were incubated in surface seawater for 11 weeks and sampled at two-week intervals. 16S rDNA sequencing and ATR-FTIR/HIM were used to assess biofilm community structure and chemical changes in polymer surfaces. The dominant colonizing taxa were previously reported cosmopolitan colonizers of surfaces in marine environments, which were highly similar among the different plastic types. However, significant differences in rare community composition were observed between plastic types, potentially indicating specific interactions based on surface chemistry. Unexpectedly, a major transition in community composition occurred in all material treatments between days 42 and 56 (p<0.01). Before the transition, Alteromonadaceae, Marinomonadaceae, Saccharospirillaceae, Vibrionaceae, Thalassospiraceae, and Flavobacteriaceae were the dominant colonizers. Following the transition, the relative abundance of these taxa declined, while Hyphomonadaceae, Rhodobacteraceae and Saprospiraceae increased. Over the course of the incubation, 8,641 colonizing taxa were observed, of which 25 were significantly enriched on specific polyolefins. 7 enriched taxa from families known to include hydrocarbon degraders (Hyphomonadaceae, Parvularculaceae and Rhodobacteraceae) and one n-alkane degrader (Ketobacter sp.). The ASVs that exhibited associations with specific polyolefins are targets of ongoing investigations aimed at retrieving plastic-degrading microbes in culture.